rho Is Not Essential for Viability or Virulence in Staphylococcus aureus - Washburn, Robert S. (American Society for Microbiology, 2001)
We have identified the gene for transcription termination factor Rho in Staphylococcus aureus. Deletion of rho in S. aureus reveals that it is not essential for viability or virulence. We also searched the available bacterial genomic sequences for homologs of Rho and found that it is broadly distributed and highly conserved. Exceptions include Streptococcus pneumoniae, Streptococcus pyogenes, Mycoplasma genitalium, Mycoplasma pneumoniae, Ureaplasma urealyticum, and Synechocystis sp. strain PCC6803, all of which appear not to possess a Rho homolog. Complementation studies indicate that S. aureus Rho possesses the same activity as Escherichia coli Rho and that the Rho inhibitor bicyclomycin is active against S. aureus Rho. Our results explain the lack of activity of bicyclomycin against many gram-positive bacteria and raise the possibility that the essentiality of rho may be the exception rather than the rule.